A Recusa do Fácil na como experiência estética na poesia de Frederico Barbosa - Busato, Susanna [UNESP] (My University, 2012)
This essay aims to drive the paths of Frederico Barbosa’s poetry to experience the refusal of the effortless. The dimensions of the emptiness, of the about and the nothing, are here under investigation as a style of expression that builds the structure of the poem. The utopian response to these themes could be in the deviation of the effortless by a refusal gesture of the language that mimetically works the paths of a style that refuses the easy way of making poetry itself.

Esta reflexão tem como objetivo trilhar a poesia de Frederico Barbosa, em termos da sua experiência poética como recusa do fácil. As dimensões do vazio, do quase e do nada são aqui objeto de investigação, uma vez que fazem parte de um estilo expressivo que constrói a estrutura do poema. A utopia do poema estaria no desvio do fácil por via de uma trajetória de recusa que se resolve na linguagem por meio de estratégias lingüísticas que mimetizam a produção ou o trajeto desse desvio.
Keywords: Frederico Barbosa; poesia contemporânea; vazio; nada; Frederico Barbosa; contemporary poetry; emptiness; nothing